2010
DOI: 10.1007/s00468-010-0509-7
|View full text |Cite
|
Sign up to set email alerts
|

Autumnal nitrogen nutrition affects the C and N storage and architecture of young peach trees

Abstract: Nitrogen fertilisation is a regular practice in orchards. Its effect on tree development, N and C acquisition and allocation were evaluated simultaneously, while coupling on the same trees in situ measurements of N uptake and shoot development and destructive determinations of organ composition in N and Total Non structural Carbohydrates (TNC). An hydroponic set-up was designed that could grow young peach trees at constant NO 3 concentration while measuring N uptake. Forty-eight trees were raised outdoors unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 29 publications
1
21
0
Order By: Relevance
“…of leaf emergence), autumnal growth was restricted to axes thickening and root development, which are despite their importance (Niederholzer et al 2001;Kaelke and Dawson 2005) only little (Kubiske et al 1998;Dong et al 2005) or not (Niederholzer et al 2001;Jordan et al 2011) affected by soil N availability. We found no difference between treatments in terms of root and old axes DW (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…of leaf emergence), autumnal growth was restricted to axes thickening and root development, which are despite their importance (Niederholzer et al 2001;Kaelke and Dawson 2005) only little (Kubiske et al 1998;Dong et al 2005) or not (Niederholzer et al 2001;Jordan et al 2011) affected by soil N availability. We found no difference between treatments in terms of root and old axes DW (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…This was probably the case in our study, because we had previously found values of between 2.6 and 3.3% DW in trees grown in similar conditions (Gomez and Jordan, unpublished). Uptake saturation may also be induced by the suppression of an important trophic sink: that relative to shoot elongation, which may represent up to 44% of the increase in autumnal biomass (Jordan et al 2011). However, these high values were obtained under exceptionally mild temperatures in young tree regrowing after severe late summer pruning.…”
Section: May 29mentioning
confidence: 97%
See 1 more Smart Citation
“…Stored N is mobilized from the roots at the beginning of the growing season and used in the development of flowers and new vegetative growth . At the end of the season, leaf N is remobilized to storage organs for use in the following season; these events are part of the N cycle in woody plants . However, stored and available soil N may not be sufficient to produce a profitable yield, necessitating application of N‐based fertilizers …”
Section: Introductionmentioning
confidence: 99%
“…In addition, increases in the yield components, such as fruit weight and diameter, which reflect greater fruit yields per plant and per hectare are expected along with impacts on fruit composition, which determine the storage period after harvest (Falguera et al, 2012). Nevertheless, the mineralization of compost in the soil will determine the responses of the peach trees and depends on the composition of the compost, including the nutrient content and C/N ratio (Jordan et al, 2011;Sofo et al, 2005). The amount of compost applied to the surface will determine the contact area with the ground, which can slow the activity of the microbial biomass (Ramos, Benítez, García, & Robles, 2011) and affect the soil moisture and soil temperature (Montanaro, Dichio, Bati, & Xiloyannis, 2012).…”
Section: Introductionmentioning
confidence: 99%